Heritage Tourism Satisfaction Toward Malacca Museums in Malaysia - Mohd Ridhuan Tee, Abdullah; Iskandar Hasan Tan, Abdullah; Mohd Masdi, Abdul Manan; Emilia, Abdull Manan (2016)
Heritage tourism has rapidly grown and one of the most income for Malaysia government. Local tourists are looking for satisfactions visiting the museum. Thus, by offering the right facilities and services that facilitate their needs, the reputation of this tourism product can be enhanced. This is supported by the findings of the study where tourists expect the museums to have greater cleanliness, well equipped safety features, nice landscape and architecture as well as an appropriate location and accessibility. This study aimed to examine the relationship between 3 elements in Levels of Tourist Satisfaction (LTS)which comprises of Travel Behavior Characteristic, Tourist Reason Visiting Museum and Museum Facilities and Services towards tourist intention in Malacca. A set of 200 questionnaires were distributed to all museumvisitors. This study applies descriptive and inferential analysis was used to identify the relationship of Travel Behavior Characteristic, Tourist Reason Visiting Museum and Museum Facilities and Services. The findings showed that all three elements in the LTS model (Travel Behavior Characteristic, Tourist Reason Visiting Museum and Museum Facilities and Services) have a relationship with tourist behavioral intention towards Malacca Museums. Thus, the findings also confirm all hypotheses. The Tourist Reason Visiting Museum was the most contributed factor that leads to intention towards Malacca Museums. Hence,Malacca Museums need to create a creative design which contains the enjoyment and fun elements besides tourist attention to other factors to visit their museum.